Analisis Perbandingan Stabilitas Keuangan Perbankan Syariah dan Konvensional di Bei periode 2021-2024 - Novita Saputri; Darwis Harahap; Sry Lestari (GLOBAL SCIENTS PUBLISHER, 2026)
Differences in operational principles between Islamic and conventional banking can lead to differences in banks' ability to maintain their financial condition. Therefore, a comparative analysis is needed to determine whether there is a difference in financial stability between the two types of banking. This study aims to analyze the difference in financial stability between conventional banking and Islamic banking listed on the Indonesia Stock Exchange during the period 2021–2024. Financial stability is an important aspect in maintaining the sustainability of banking operations and increasing public trust in the national financial system. In this study, financial stability is measured using three main indicators, namely Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio/Financing to Deposit Ratio (LDR/FDR). The research method used is a quantitative approach by utilizing secondary data in the form of annual financial reports obtained from each banking company. The population in this study consists of forty-seven Islamic and conventional banking populations on the IDX and the research sample consisted of eight banks, which included four conventional banks and four Islamic banks. The data analysis techniques are carried out through several stages, namely descriptive statistical analysis to describe the characteristics of the data, normality test using the Shapiro-Wilk method, and difference tests using the Mann-Whitney U Test because the data is not normally distributed. The results of the study showed that in the Return on Assets (ROA) variable, there is a significant difference between conventional banking and Islamic banking. Meanwhile, in the variables Capital Adequacy Ratio (CAR) variable there is a significant difference and the Loan to Deposit Ratio/Financing to Deposit Ratio (LDR/FDR), there is a significant difference between the two types of banking. These findings show that financial stability between conventional banking and Islamic banking has a really different in all indicators usud in the study. These differences indicate that each type of banking has difference characteristics and levels of financial performance, both in terms of profitability, capital adequacy, and liquidity.